G450(P) Focal seizures: An unusual cause. (7th April 2014) - Varughese, R; Bandaranayake, G; Mathew, A
Abstract : Aims: The aim of this case report is to highlight the management of focal seizures and demonstrate how routine investigations reveal an unusual aetiology. Introduction: An 11-year-old boy presented with focal seizures and dyscognitive symptoms. His birth was uneventful, development normal. There was no family history of epilepsy. Examination revealed several right-sided facial features; a vertical linear indentation extending from brow to hairline (linea morphea), subtle hemi-facial atrophy with fewer lashes to the right eye, pronounced tongue hemi-atrophy. Systemic examination including neurology was normal. Methods: Electroencephalography (EEG), Magnetic resonance imaging (MRI) Brain and Thermography of the face were performed. Results: EEG did not show definitive features of epilepsy. MRI revealed extensive white matter changes in the right cerebral hemisphere with multifocal areas of calcification. Thermography revealed minimal increase in temperature over the linea morphoea reflecting increased heat conduction through thinned tissues. The combination of hemi-facial atrophy and unilateral brain parenchymal changes favoured the diagnosis of Parry Romberg syndrome. He was later treated with Carbamazepine and Levtiracetam. Methotrexate was considered. Both demonstrating Extensive white matter change in the right cerebral hemisphere containing multifocal areas of calcification with negligible mass effect. Conclusion: Parry Romberg syndrome (PRS) is a rare acquired disease characterised by progressive hemi-facial atrophy, which can extend into subcutaneous tissue, muscle and bone. It may present with features reminiscent of 'en coup de sabre' (ECDS) and together they are postulated to be variants of the localised scleroderma spectrum of disease (1) (2). 'Coup de sabre' means 'cut of the sword', referring to the linear sclerotic plaque seen on the scalp of affected patients. PRS is a disorder associated with a variety of neurological manifestations including seizures (3). Ophthalmologic and maxillofacial abnormalities may co-exist. The aetiology is unknown although trauma, genetic factors, and autoimmune pathology have been postulated. Severity of the superficial disease does not predict intracranial abnormalities. An MRI to assess for neurologic involvement, despite absent neurological symptoms guides further management (4). PRS usually manifests in the first or second decade of life (5). Characteristic progression involves rapid development over the first two to ten years, followed by remission (6). Immunosuppressive therapy (7) and reconstructive surgery after remission is used for symptomatic control. When assessing children with common presentations, investigations sometimes reveal rare and unusual conditions.